Changes in Non-Structural Carbohydrates, Wood Properties and Essential Oil During Chemically-Induced Heartwood Formation in Dalbergia odorifera - Cui, Zhiyi; Li, Xiaofei; Xu, Daping; Yang, Zengjiang (Frontiers in Plant Science, 2020)
The highly valuable heartwood of Dalbergia odorifera T. Chen, known as Jiang Xiang in traditional Chinese medicine, is formed very slowly, and there is a need to better understand the process and promote heartwood formation. Chemical induction is considered to be one of the promising methods to induce heartwood formation. However, to date no method has been proved effective for D. odorifera as little is known about biochemical and physiological changes during heartwood development. Three potential heartwood induction substances viz. acetic acid, sodium chloride, and hydrogen peroxide solutions were injected into the trunk of D. odorifera to determine the effect on heartwood formation and physiological activity. Non-structural carbohydrates, lipids, wood properties, and essential oil were assessed in the post-treatment period. As also observed in the formation of natural heartwood, chemical-induced Jiang Xiang production was accompanied by sapwood dehydration, non-structural carbohydrates consumption, and synthesis of heartwood substances. As the heartwood substances accumulated, basic density and essential oil content increased gradually, thereby Jiang Xiang was finally produced. In this process, physiological parameters of discolored sapwood gradually evolved to resemble those of natural heartwood. Hydrogen peroxide-induced Jiang Xiang was closest to natural heartwood, and the essential oil components met the standards for high-quality Jiang Xiang, while the induction effects of acetic acid and sodium chloride were unsatisfactory. Thus, this study indicates that hydrogen peroxide has the potential to induce Jiang Xiang production in Dalbergia odorifera.